Reiterated Concerns and Further Challenges for Mindfulness and Meditation Research: A Reply to Davidson and Dahl. (January 2018) - Van Dam, Nicholas T.; van Vugt, Marieke K.; Vago, David R.; Schmalzl, Laura; Saron, Clifford D.; Olendzki, Andrew; Meissner, Ted; Lazar, Sara W.; Gorchov, Jolie; Fox, Kieran C. R.; Field, Brent A.; Britton, Willoughby B.; et al.
In response to our article, Davidson and Dahl offer commentary and advice regarding additional topics crucial to a comprehensive prescriptive agenda for future research on mindfulness and meditation. Their commentary raises further challenges and provides an important complement to our article. More consideration of these issues is especially welcome because limited space precluded us from addressing all relevant topics. While we agree with many of Davidson and Dahl's suggestions, the present reply (a) highlights reasons why the concerns we expressed are still especially germane to mindfulness and meditation research (even though those concerns may not be entirely unique) and (b) gives more context to other issues posed by them. We discuss special characteristics of individuals who participate in mindfulness and meditation research and focus on the vulnerability of this field inherent in its relative youthfulness compared to other more mature scientific disciplines. Moreover, our reply highlights the serious consequences of adverse experiences suffered by a significant subset of individuals during mindfulness and other contemplative practices. We also scrutinize common contemporary applications of mindfulness and meditation to illness, and some caveats are introduced regarding mobile technologies for guidance of contemplative practices.